Laboratory diagnosis of 44 cases of pediatric histiocytic necrotizing lymphadenitis - Jin, Jingjing; Lu, Songjian; Lin, Honghua (Frontiers in Pediatrics, 2025)
ObjectiveTo investigate the clinical features, laboratory findings, treatment, and follow-up of pediatric histiocytic necrotizing lymphadenitis (HNL) to enhance understanding of this disease.MethodsA retrospective analysis was conducted on clinical data of 44 pediatric patients diagnosed with histiocytic necrotizing lymphadenitis (HNL) who were admitted to our hospital from January 2018 to October 2024. The clinical features, laboratory findings, pathological results, treatment, and prognosis were examined.Results44 patients, aged 4–14 years (mean age: 9.4 ± 2.6 years), including 28 males and 16 females, Among them, 41 patients (93.2%) were aged ≥6 years. All patients presented with fever and superficial lymphadenopathy. Other clinical manifestations comprised rash (10 cases, 22.7%), abdominal pain and vomiting (7 cases, 15.9%), hepatosplenomegaly (5 cases, 11.4%), weight loss (3 cases, 6.8%), and fatigue (3 cases, 6.8%). The clinical manifestations of HNL (e.g., fever, cervical lymphadenopathy) were nonspecific and overlapped with other pediatric conditions. Definitive diagnosis required lymph node biopsy, which consistently demonstrated HNL in all cases. Laboratory findings predominantly showed normal or reduced leukocyte counts (42 cases, 95.5%), elevated lactate dehydrogenase (LDH) (38 cases, 86.4%), increased erythrocyte sedimentation rate (ESR) (34 cases, 77.3%), and elevated D-dimer levels (28 cases, 63.6%). Lymph node ultrasound (36 cases, 81.8%) revealed hypoechoic nodules, while neck CT (7 cases, 15.9%) demonstrated nodular soft-tissue density shadows. Glucocorticoids were administered to 35 cases (79.5%). Two cases (4.5%) of secondary hemophagocytic lymphohistiocytosis (HLH) were treated with methylprednisolone pulse therapy or intravenous immunoglobulin. Three cases (6.8%) were administered glucocorticoids combined with disease-modifying antirheumatic drugs, 1 case (2.3%) received nonsteroidal anti-inflammatory drugs (NSAIDs) alone, and 8 cases (18.2%) resolved spontaneously without intervention. During a follow-up period ranging from 2 months to 6 years, no cases progressed to other rheumatic diseases, 5 cases (11.4%) experienced recurrence, whereas the other cases exhibited a satisfactory prognosis.ConclusionThe clinical manifestations of HNL in pediatric patients are nonspecific, necessitating lymph node biopsy for definitive diagnosis. It is glucocorticoid-sensitive, and some cases may resolve spontaneously with a positive prognosis, but long-term monitoring is essential.